CHALLENGES AND OPPORTUNITIES FOR SMEs IN DEVELOPING MODERN CULINARY - M. Hafidh Nashiruddin Al-Bakry (Riviera Publishing, 2024)
This study analyzes the challenges and opportunities SMEs face in developing their culinary business in North Sumatra. The qualitative method used in this research involves interviews and observations of 15 participants who are SMEs in the culinary field. The study results show that SMEs in North Sumatra face several challenges in developing their culinary business. The main challenges faced are intense competition in the modern culinary industry, limited resources, and consumer changes. However, this research also found that there are opportunities that SMEs in North Sumatra can exploit. The main opportunities found are the developing tourism potential in this area, technology, and social media that are easy to use as promotional tools, and opportunities to work together and collaborate with other SMEs to develop modern culinary delights in North Sumatra. From this research, it is hoped that SMEs' courage, creativity, and ability to adapt to market changes will succeed in developing their culinary business in North Sumatra.